EFEK PEWARNAAN RAMBUT DARI EKSTRAK KULIT UMBI UBI UNGU (Ipomoea batatas L.) DENGAN VARIASI KONSENTRASI CU SULFAT SEBAGAI PEMBANGKIT WARNA - Mindiya Fatmi; Septia Andini; Rini Ambarwati; Ikrom Khaulah (Jurnal Insan Farmasi Indonesia, 2023)
Hair dye is a cosmetic preparation intended to give the hair a new color or restore the original color. Purple sweet potato tuber skin contains more anthocyanin that can be used in the manufacture of hair dye preparations. The extract was prepared by maceration using 96% ethanol. Hair dyes were made into 4 formulas: Formula 0 was not added with a concentration of copper II sulfate, while Formulas 1, 2, and 3 were added with copper II sulfate concentrations of 0.5%, 1%, and 1.5%. The tests included organoleptic tests, homogeneity, pH, viscosity, hair coloring stability tests, including stability tests against washing and sunburn, and preference tests. The results showed that the hair dye gel preparations were homogeneous, had a distinctive odor of hair dye, and had brown (F0), brownish green (F1), and blackish green (F2 and F3) colors. The pH of the preparation ranged from 4.6 to  6.3, and the viscosity test ranged from 8243.5-8583.5 Cp. In the staining stabili